(untitled) (Academicia Globe: Inderscience Research, 2024)
Heavy metals already occupy the second place in terms of degree hazards, yielding to pesticides and well ahead of well-known pollutants such as carbon dioxide and sulfur. In the future, they can become more hazardous than nuclear waste and solid waste. Heavy metals contamination is associated with their widespread use in industrial production. Due to imperfect cleaning systems heavy metals enter the environment, including the soil, polluting and poisoning it. Heavy metals refers to special pollutants, observations which are required in all environments.